Assessment of water quality parameters, biomaginfication studies of selected heavy metals and characterization of solid wastes in Sungai Pencala / N. Lakshmi Praba - Praba, N. Lakshmi (2009)
The study was conducted to assess the extent of pollution in Sungai Pencala. A total of 14 monitoring stations were established along the river. The selected sampling stations represented the various activities in the surroundings of Sungai Pencala. Samplings were conducted 12 times over a period of 16 months from March 2006 – June 2007. Water quality parameters such as temperature, pH, DO, BOD, COD, NH3-N, conductivity, tubidity, TSS, TDS, TBC, and E Coli were monitored to determine the pollution status of the river. The results were then compared to the current recommended Interim National Water Quality Standards for Malaysia (INWQS) and DOE Water Quality Criteria for Malaysia. Apart from water, fish and plant samples were also analyzed for selected heavy metals such as, cadmium, chromium, lead and mercury to assess the bioaccumulation of those metals. Heavy metals were analyzed using Inductively Coupled Plasma –Mass Spectrometry (ICP MS) and Flow Injection Mercury Analyser (FIMS). Analysis of certified reference material (CRM) from National Research Council Canada (DOLT 2) showed good agreement with the certified values for all selected metals, obtaining more than 84% recovery. Solid waste characterization was also carried out at few selected locations. This study reveals that Sungai Pencala needs a better management and development in order to provide better ecosystem to support healthy aquatic life.